THE ROLE OF BIOLOGICAL AND SOCIAL FACTORS IN DETERMINING GENDER IDENTITY - M. I. Boichenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The aim of this article is an analysis of the main versions of the biodeterminist tradition of resolving the issue of the nature of gender identity, as well as identification of the advantages of the new version of biodeterminism, which involves elements of social constructivism. Theoretical basis. Social norms determine the extent to which a person has the right to independently determine his or her gender identity, and even more so, to change his or her body according to such gender concepts. Social norms regulate gender relations in society and direct the gender behavior of individuals. However, social norms do not create either the human body, or those biological laws, according to which it functions. Originality. The biodetermist theories of the gender were analyzed from the position of "week" social constructivism. The role of social norms as a factor of gender self-certification, as well as a factor of control over social interference in the functioning of human corporeality is considered. The role of modern medicine as an increasingly influential institutional means of control over the functioning of human corporeality, and therefore, indirectly, and for the implementation of gender identity self-identification is revealed. Conclusions. According to the "week" social constructivism the gender emerges as an integral result of biological, psychological and social construction. The role of personality in the design of the gender has historically grown, but this role can never exclude the influence of biological and social factors that are increasingly becoming the nature of biological and social technologies. Personality can become a victim of these technologies, but he/she can program them, or at any rate selectively use, combine, or to some extent adjust existing biological and social technologies.